CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY AND BIOCHRONOLOGY IN EASTERN MEDITERRANEAN DEEP-SEA CORES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
A study of calcareous nannofossils was carried out, using an optical microscope, on a set of eastern Mediterranean deep-sea cores. These cores were mainly colleced during cruise MD69, organized within the framework of the MAST-Marflux project. The main purposes of this paper are the assessment of a preliminary stratigraphy of "old" sapropels (i.e. never recovered in piston cores prior ro cruise MD69), the quantitative recognition of biostratigraphic events and their calibration with respect to magnetostratigraphy and isotope/faunal stages. Nannofossil biostratigraphy demonstrates that sapropels are present in the Pseudoemiliania lacunosa and in the underlying small Gephyrocapsa nannofossil zones. These findings are of key importance to link the deep- sea record to that of land sections (Calabria and Sicily, Southern Italy), where sapropelitic layers are present up to the large Gephyrocapsa/small Gephyocapsa zonal boundary. The beginning of the E. huxleyi Acme is calibrated with isotope/faunal stage 4. Based on astronomical dating of sapropels S1 (8 ka) and S3 (79 ka), this event is estimated to 51 +/- 2 ka (core Ban88-11GC) or 54 +/- 5ka (core Ban82-15PC). The E. huxleyi  FAD cannot be confidently detected using the optical microscope technique. The LAD of P. lacunosa is estimated to 468 ka, based on interpolation between the Brunhes/Matuyama magnetic boundary (780 ka) and sapropel S9 (238 ka). With the same procedure the disappearance of Gephyrocapsa sp.3 (sensu Rio, 1982) from the Mediterranean is estimated to 584 ka. The FAD of Gephyocapsa sp. 3 and the "re-entrance" of medium sized Gephyrocapsa define the top of the small Gephyocapsa Zone, which is demonstrated to occur shortly after the end of the Jaramillo magnetic event in the Mediterranean area, with an interpolated age of 944 ka. An "acme" event of small Gephyrocapsa, beginning close to sapropel S9, is correlated with isotope stage 8 and dated as 265 ka.
Keywords: Stratigraphy; Quaternary; Eastern Mediterranean; Calcareous nannofossils.